Efektifitas Iklan YouTube: Korelasi antara Kredibilitas Tasya Farasya dengan Ulasan Produk Maybelline - Putri, Triana; Rayhan, Muhammad; Marta, Rustono Farady; Ahmad, Rosmalia; Harliyono, Maria (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
Influencers can strengthen the effectiveness of advertising by consumers when they are considered to have good credibility, so they buy the product. The aim of the research is to determine the relationship between Tasya Farasya's credibility and the effectiveness of Maybelline product reviews as marketing communication strategy.Â  Previous study of Credibility Theory by Hovland & Weiss found that audiences tend to give a higher level of approval when the source has a high reputation. There are two variables that will be measured, namely source credibility and review effectiveness. Source credibility is measured using the dimensions of attractiveness, trustworthiness, and expertise. Also, advertising effectiveness is measured using the dimensions of personal engagement and interactive engagement. The research used a survey-based explanatory quantitative approach by distributing questionnaires to 100 consumers of Maybelline products. The data obtained was processed using SPSS version 27 software, and analyzed by correlation. Research findings show that there is a significant and strong relationship between Tasya Farasya's credibility and the effectiveness of Maybelline product advertising. Therefore, it can be concluded that Tasya Farasya's credibility is able to strengthen the effectiveness of Maybelline product advertising.